Study of Toxic Effect of Crud Colicin Exracted from Escherchia Coli on Viability of Immune Cells. - Essa, R; Hussain, H; A I Mohymen, N. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Crude-colicin was extracted from g.coli isolated from urinary tract infection patients. Toxicity of various concentrations of crudt: colicin on the viability of immune cells [phagocytic ceUs(M0,PMN) and lymphocytes] was studied. Results indicated that toxicity ciTect of crude colicin is dependent on concentration. Low concentrations (I0, 25, 50 mg/ml) didn’t have toxic effects, but when there was an increase in the consternation of this extract, the viability of the immune cell s began to decrease.